Women’s Access to Education in Nepal: Intergenerational Change - Mishra, Mira (Dhaulagiri Journal of Sociology and Anthropology, 2013)
This paper describes intergenerational changes in women’s access to education in Nepal. It links up the changes with changing socio-economic processes and suggests that women’s access to education is increasing by generation. And by linking up Anthony Giddens’s Structuration Theory (1984) with the finding, the paper shows the interplay of both structure and agency in bringing changes in women’s access to education. This paper also shows the rural urban differences in access to education and links up between marriage and education. The paper begins with the brief introduction of Nepal and Nepali women, goes on to theoretical arguments on structure and agency debate, and then describes methodology and characteristics of 39 women interviewees and discusses changes. DOI: http://dx.doi.org/10.3126/dsaj.v6i0.8478 Dhaulagiri Journal of Sociology and Anthropology Vol. 6, 2012 49-60